Analysis of Risk Factors for Antimicrobial Resistance in Bacterial Infections among Diabetic Foot Ulcer Patients - William, Andrew; Sembiring, Yan Efrata; Widodo, Agung Dwi Wahyu; Novida, Hermina (Universitas Airlangga, 2025)
Introduction: Diabetic foot ulcer (DFU) is a chronic and progressive complication of diabetes mellitus resulting from macroangiopathy and microangiopathy disorders. Acknowledging the relationship between the Wagner diabetic foot ulcer classification system and infection severity may offer a promising instrument for guiding empirical antibiotic selections in clinical settings. This study aimed to assess the relationship between Wagner grades and the pathogen profiles of patients with DFU, along with their susceptibility to antibiotic therapy.Methods: A cross-sectional study was conducted from January 2021 to August 2023, utilizing 33 secondary datasets obtained from electronic medical records. The data contained the patients' Wagner grades alongside the results of their complete microbiological analysis and antibiotic susceptibility test. The association between determinant factors and patients' pathogen profiles and antibiotic susceptibility patterns was examined using the Chi-square bivariate analysis (p<0.05).Results: Positive culture results were observed in 32 patients (97%), with 59% exhibiting resistance to first-line antibiotics. The most commonly isolated pathogen was Staphylococcus aureus. The antibiotic susceptibility patterns indicated that gentamicin-syn demonstrated the highest activity against Gram-positive bacteria (GPB) isolates, while erythromycin was the most effective against Gram-negative bacteria (GNB) isolates. With escalating Wagner grades, there was an increased proportion of mixed infections, GNB infections (n=8, X²=23.28, p=0.003), and antibiotic resistance (n=8, X²=39.97, p=0.000). GNB isolates showed higher resistance compared to GPB isolates (n=18, X²=42.15, p=0.001).Conclusion: Our findings suggest that DFU patients with varying Wagner grades exhibit different bacterial profiles, infection patterns, and antibiotic sensitivities. Highlights:1. This is the first study conducted in Indonesia to analyze the relationship between the Wagner diabetic foot ulcer classification system and patients' pathogen profiles and antimicrobial susceptibility.2. This study incorporated an in-depth analysis of several infection patterns and the occurrence of antimicrobial resistance, hence offering valuable information on the application of the Wagner classification system not only as a tool for grading infection severity but also for guiding clinicians in selecting the appropriate antibiotics for patients with diabetic foot ulcers.